For Polanyian Economic Geographies - Peck, Jamie (Environment and Planning A, 2013)
Karl Polanyi has been an influential but also somewhat elusive figure in economic geography. Best known for his evocative notion of social embeddedness, it is perhaps fitting that Polanyi's presence has been more metaphorical than substantive. The paper asks what a more engaged Polanyian economic geography might look like. Focusing on methodological affinities, a response is developed in terms of a commitment to the substantivist (as opposed to formal) analysis of actually existing economic formations, together with a more purposive embrace of institutionalism, holism, and comparativism.
Keywords: comparative economy; economic geography; institutionalism; substantivism